2020
DOI: 10.1364/oe.384127
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of AlGaInP red micro-light-emitting diodes with sidewall treatments

Abstract: The electrical and optical improvements of AlGaInP micro-light-emitting diodes (µLEDs) using atomic-layer deposition (ALD) sidewall passivation were demonstrated. Due to the high surface recombination velocity and minority carrier diffusion length of the AlGaInP material system, devices without sidewall passivation suffered from high leakage and severe drop in external quantum efficiency (EQE). By employing ALD sidewall treatments, the 20×20 µm2 µLEDs resulted in greater light output power, size-independent le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 30 publications
1
93
1
Order By: Relevance
“…This method can easily integrate RGB colors into matrices on the same substrate [7], yet the colorconversion efficiency of hybrid devices must be improved [8]. Another approach chooses to fabricate red and green µLEDs using different materials, AlInGaP for red µLEDs [9] and InGaN for green µLEDs [10]. This material difference causes a mismatched angular distribution between the red and green µLEDs [11], leading to a noticeable color shift at different observed angles.…”
mentioning
confidence: 99%
“…This method can easily integrate RGB colors into matrices on the same substrate [7], yet the colorconversion efficiency of hybrid devices must be improved [8]. Another approach chooses to fabricate red and green µLEDs using different materials, AlInGaP for red µLEDs [9] and InGaN for green µLEDs [10]. This material difference causes a mismatched angular distribution between the red and green µLEDs [11], leading to a noticeable color shift at different observed angles.…”
mentioning
confidence: 99%
“…It was also shown that the surface recombination through Shockley‐Read‐Hall (SRH) recombination via defect levels is dominant in the smaller red LEDs. So the decrease in EQE is much more significant for red micro‐LEDs smaller than 10 μm, 16 although some improvement can be expected by surface treatment and sidewall passivation 25 …”
Section: Resultsmentioning
confidence: 99%
“…[ 10,13–29 ] For instance, Figure a–c exhibits the EQEs of different size red, green, and blue LEDs as a function of current density. [ 17,19,22 ] The maximum EQE decreases with decreasing LED size and the maximum EQE is obtained at higher current densities as chip size decreases. This behavior has been ascribed to leakage current and/or Shockley–Read–Hall (SRH) nonradiative recombination caused by sidewall defects in smaller chip geometries.…”
Section: Size Dependence Of Electrical and Optical Performancementioning
confidence: 99%
“…[ 13,17,25 ] The ideality factors were assessed using the current–voltage curves. Measurements of red AlGaInP‐based, and green and blue InGaN‐based LEDs showed that smaller devices had higher ideality factors, [ 17,19,22 ] indicating they suffered from carrier loss due to SRH nonradiative recombination at sidewall defects. [ 18,19,25 ] Further, the green and blue LEDs typically exhibit the maximum EQE at lower current than the red LEDs.…”
Section: Size Dependence Of Electrical and Optical Performancementioning
confidence: 99%